Impact of COVID-19 Pandemic Burnout on Cardiovascular Risk in Healthcare Professionals Study Protocol: A Multicenter Exploratory Longitudinal Study - Al Tunaiji, Hashel; Al Qubaisi, Mai; Dalkilinc, Murat; Campos, Luciana Aparecida; Ugwuoke, Nnamdi Valbosco; Alefishat, Eman; Aloum, Lujain; Ross, Ramzy; Almahmeed, Wael; Baltatu, Ovidiu Constantin (Frontiers in Medicine, 2020)
Introduction: The coronavirus disease 2019 (COVID-19) pandemic has created new and unpredictable challenges for healthcare systems. Healthcare professionals are heavily affected by this rapidly changing situation. They may experience psychological burden, especially nurses, women, and frontline health care professionals directly engaged in the diagnosis, treatment, and care for patients with COVID-19. The objective of this study is to investigate the evolution of psychosocial, cardiovascular and immune markers in healthcare professionals with different levels of exposure to the COVID-19 pandemic. The effects of the pandemic work burden on psychological, cardiovascular and immune biomarkers will be stratified per level of exposure to the COVID-19 pandemic, positive diagnosis to COVID-19, profession, sex, age and already existent cardiovascular risk. Methods: A STROBE compliant, blended exploratory study involving online and onsite approach with wearable monitoring will be implemented. A planned random probability sample of residents, staff physicians, nurses and auxiliary healthcare professionals will be recruited from both inpatient and outpatient medicine services. The study sample will be stratified by exposure to the COVID-19 pandemic (frontline versus second line). As a first step, recruitment will be conducted online, with e-consent and e-survey with Maslach Burnout Inventory, Fuster-BEWAT score and sociodemographic characteristics, during this, an onsite visit will be planned for the second step where participants will receive a setup for wearable heart rate, actimetry and sleep quality monitoring together with blood sampling for immune biomarkers. Steps 1 & 2 will then be repeated at 2-3 months, and 6 months. Power BI & Tableau will be used for data visualization purposes, while the front-end data capture application will be used for data collection and will be built using specific survey/questionnaire related tools for healthcare usage data linkage. Ethics and dissemination: Institutional Review Board approval has been obtained from Khalifa University (protocol # CPRA-2020-034) and Department of Health-Abu Dhabi (protocol # CVDC-20-05/2020-8). Data analysis, release of results and publication of manuscripts are scheduled to start in early 2021. Data and findings may be useful to healthcare policymakers for developing preventive strategies to reduce or prevent burnout, cardiovascular risk and immune dysfunction.